Sheathless inertial particle focusing methods within microfluidic devices: a review - Peng, Tao; Qiang, Jun; Yuan, Shuai (Frontiers in Bioengineering and Biotechnology, 2024)
The ability to manipulate and focus particles within microscale fluidic environments is crucial to advancing biological, chemical, and medical research. Precise and high-throughput particle focusing is an essential prerequisite for various applications, including cell counting, biomolecular detection, sample sorting, and the enhancement of biosensor functionalities. Active and sheath-assisted focusing techniques offer accuracy but necessitate the introduction of external energy fields or additional sheath flows. In contrast, passive focusing methods exploit the inherent fluid dynamics to achieve high-throughput focusing without external actuation. This review analyses the latest developments in sheathless inertial focusing strategies, emphasizing inertial and elasto-inertial microfluidic focusing techniques from the channel structure classifications. These methodologies will serve as pivotal benchmarks for the broader application of microfluidic focusing technologies in biological sample manipulation. Then, prospects for future development are also predicted. This paper will assist the understanding of the design of microfluidic particle focusing devices.